The disintegration of the Austro-Hungarian army in 1918 - Michał Baczkowski (Folia Historica Cracoviensia)
The internal disintegration of the Austro-Hungarian army in 1918 was one of the chief causes of not only the defeat of the Habsburg monarchy in the First World War but also of the breakup of the dual state. That long-term process began in the winter of 1917/18 with the shortages in supplies for the soldiers. Its dynamic was strongly boosted by the return of prisoners of war from Russian captivity on the power of the peace treaty of Brest-Litovsk (March–October 1918), and the defeat by the Piave (July 1918). There were increasing instances of marauding and local rebellions in the rear ranks from the spring of 1918 resulting in the breakdown of discipline and a huge wave of desertions in the summer of that year. The response of the authorities was poor for fear of a civil revolution or a rebellion stimulated by the national context in the event of a brutal use of force. The weakened army limited its activity on the front, passively awaiting the signing of a peace. The last phase of the demise came in October 1918 and resulted from the lack of faith in a quick conclusion to the conflict combined with the hopes of rank-and-file soldiers for the establishment of national states on the wreckage of Austria-Hungary, which was to result in immediate termination of hostilities. In such circumstances, the beginning of the Italian offensive at Vittorio Veneto led to a series of rebellions of line troops. This caused the collapse of the front, the unauthorised return of entire corps to their homes, and the signing of the Armistice of Villa Giusti by the declining monarchy and capitulation to the conditions of the on Italians.